Persepsi Pembaca Pada Brosur Pariwisata Di Kabupaten Bangkalan - Galuh Tri Meilani; Sriyono Sriyono (Journal of Social, Culture, and Language, 2022)
The purpose of this study is to identify the perceptions of readers as students of Universitas Trunojoyo on travel brochures by the Tourism and Culture Office of Bangkalan Regency. The method used in this research is descriptive qualitative. This method aims to describe the phenomenon of brochures being investigated. Data collection techniques used are direct interviews, questionnaires, documentation, and, literature review. The total population in this study are 12 respondents with several questions relevant to the topic of this research. Keywords: Perception; Madura Tourism; Travel Brochure